ANALISIS KESULITAN SISWA KELAS VIII DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMP NEGERI 2 AMANDRAYA - Ardibudi Laia (Universitas Nias Raya, 2024)
This research was motivated by mistakes made by Class XI-MIA students at Teluk Dalam Campus Private High School when completing matrix questions. The purpose of this research is to find out students' mistakes in solving matrix questions. This type of research is qualitative research with a descriptive approach. The informants in this research were 30 students in class XI-MIA of the Teluk Dalam Campus Private High School. Data were analyzed using data reduction steps, data presentation, and drawing conclusions. The data collection techniques used were tests and interviews. The results of this research from all student answers show that students made 15% factual errors, 49.7% conceptual errors, 30.7% principle errors, and 4.6% operational errors in this study. So it can be concluded that class XI-MIA students at Teluk Dalam Campus Private High School made the highest number of mistakes, namely conceptual errors. Based on these results and conclusions, the researcher suggests that students do questions more often and understand the concepts in the matrix material so that they are used to and understand how to solve the questions given.